THE SIGNIFICANCE OF ISLAMIC ECONOMICS STUDY IN DISCIPLINE OF MODERN ECONOMICS - Suryani, Suryani (Journal of Indonesian Economy and Business, 2012)
The development of Islamic economic practices in Indonesia shows an encouraging fact. Since the last fifteen years, the development of Islamic economic discourses in Indonesia has attracted the attention of many academicians and practitioners. From the academic view, the development of Islamic economics is marked by many educational institutions that offer training programs and courses of Islamic economics. Islamic economics study should lead to formation and internalization of Islamic values in the economiclife. Therefore, the suitable teaching method to increase the quality of Islamic economics is competency-based curriculum that combines textual and contextual approach. Both approaches should be incorporated in formal and nonformal education. Thus the development of Islamic economics are expected to line between conceptual and business practices in accordance with recent guidance that will eventually form an Islamic economic system truly in accordance with basic principles of sharia.Keywords: education, islamic economics.